ONE-DIMENSIONAL ANALYSIS OF MAGNETIC DIPOLE CYLINDER INSIDE AN EXTERNAL MAGNETIC FIELD - BRAM YOHANES SETIADI (NIM : 10212011),
Electromagnetism has evolved from only a science into an unseparated part of our daily life, nowadays. One kind of benefit that still on development process is the use of magnetic field as a energy source of any physical movements. A movement analysis system was designed and built in this experiment. It consists of a solenoid, two cylinders made from acrylic and were injected by a chip magnet(s), and a rail track or container for the cylinder. The goal of this research is to observe and specify the types of movement which produce by the cylinder as a reponse of external magnetic field from the solenoids. The dependent variables include starting position and starting angle of the cylinder, the amount of magnet chip injected inside it, and the voltage used to supply the solenoids. Combinations between translational and rotational motion come as a result of this experiment, in other words, rolling motion. Rolling motion that observed is divided into two types, pure and with slipping, while rolling with slipping still divided again into translationan dominance and rotational dominance.